Exploring the operator experience in automated shuttles: Fatigue, attention, and gaze behaviour - Christer Ahlström; My Weidel; Anna Sjörs Dahlman; Ashleigh Filtness; Anna Anund (Transportation Research Interdisciplinary Perspectives, 2025)
Automated shuttles provide a first look at future transportation, however, they still require on-board human operators for regulatory compliance and safety assurance. This paper examines the experiences of eight shuttle operators through two studies. The aim was to investigate their alertness throughout their working shifts. Study A used a controlled experimental methodology to compare fatigue and gaze behaviour at complex road sections during the first and last hours of one shift. Study B involved naturalistic observations over two months, examining sleep, sleepiness and stress.Study B found that 27% of work shifts occurred following less than six hours of sleep. However, only 1% of shifts resulted in a Karolinska Sleepiness Score of 7 or higher, suggesting that insufficient sleep was rare. Stress was also infrequently reported. Notable individual differences suggested the potential value of personalized approaches to fatigue management. Study A revealed that while overall alertness was generally adequate, gaze patterns often deviated from safe expectations. Operators paid less attention to their surroundings than would be expected (21% not looking left, 38% not looking right, 58% not looking to the rear of the vehicle, in situations where this would have been appropriate).The results are important for safety operators and their employers, highlighting the shared responsibility of having well-prepared and well-rested operators who are fit to effectively monitor the automated shuttle for an entire driving period. Further research is needed to develop effective strategies to maintain operators’ situational awareness over time, especially as their confidence in the vehicles’ capabilities increases.